People’s Participation in Environment Management of Suan Luang District Office Bangkok Metropolis - Daokongkaew, Sarawut; Sangern, Thaveesak; Boonsermwan, Sarojn; Sriboonrueang, Ampika; Kumlur, Hadsayarat (Rajapark Journal, 2022)
The objectives of this research were to 1) study the level of people’s participation in the environmental management of the Suan Luang District Office; 2) compare their participation classified by personal factors; and 3) study problems, obstacles, and recommendations for people's participation in environmental management. 123,609 people living in Suan Luang District were the target population, and 400 of them were selected as the study samples by means of a simple random sampling technique. Questionnaires with a confidence value of 0.87 were used for collecting data. Frequency, percentage, mean, and standard deviation were used for data analysis. The results of this research were as follows: The overall people’s participation in the environmental management of Suan Luang District Office was at a moderate level ( = 3.27). Accordingly, in terms of each aspect of their participation, according to the means ranked from the highest to the lowest were decision making, operation, and benefit assessment respectively. There were no significant differences among the opinions of people with different average monthly incomes and lengths of living in the community, whereas there were significant differences at 0.05 among the opinions of those with different genders, ages, education levels, and careers.